The Effect of Perception of Usefulness, Perception of Ease of Use, Intention to Use on the Use of the M-Passport Application at the Class I Immigration Office, Special TPI, Makassar: JEL Classification: H83, O33, O38, M15 - Budi Prasetya; M. Nasir Hamzah; Nurmadhani Fitri Suyuthi (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The objectives of this study are 1) To analyze and examine the effect of Perceived Usefulness on the use of the M-Paspor application at the TPI Makassar Class I Special Immigration Office. 3) To analyze and examine the effect of Perceived Usefulness on the Intention to Use the M-Paspor application at the TPI Makassar Special Class I Immigration Office. 4) To analyze and examine the effect of Perceived Ease of Use on the Intention to Use the M-Paspor application at the TPI Makassar Special Class I Immigration Office. 5) To analyze and examine the effect of Intention to Use on the use of the M-Paspor application at the TPI Makassar Special Class I Immigration Office. The research approach used is quantitative-descriptive. This study was conducted at the TPI Makassar Special Class I Immigration Office, with the research subjects being passport applicants at the office, and a total sample size of 102 respondents. Data collection techniques included observation, questionnaires, and documentation. The findings show that Perceived Usefulness has a significant effect on the use of the M-Paspor application. Perceived Usefulness also has a significant effect on the Intention to Use the M-Paspor application. Perceived Ease of Use has a significant effect on the use of the M-Paspor application. Perceived Ease of Use also has a significant effect on the Intention to Use the M-Paspor application. Furthermore, Intention to Use has a significant effect on the use of the M-Paspor application.